Bleak House - Dickens, Charles (Lawrence, KS : Digireads.com Publishing (a subsidiary of Neeland Media LLC), 2009)
With their estate entangled in an interminable legal case, the young wards of the court Richard Carstone and Ada Clare are taken into the benevolent care of the kindly John Jarndyce. Ada's companion, the gentle and good-hearted Esther Summerson, is devoted to the old man and, although she loves another, becomes betrothed to him. But behind Esther's supposed orphan past lies a dark secret that leads tragically to deceit, blackmail and murder. And as the endless lawsuit erodes their inheritance, the happiness that Richard and Ada have found in each other is brought into desperate jeopardy.
Keywords: Dickens, Charles, -- 1812-1870.; Illegitimate children; Guardian and ward; Young women; London (England); Domestic fiction; Legal stories